2014
DOI: 10.1530/rep-13-0405
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin deprival modifies follicular and corpus luteal growth dynamics in a sheep model

Abstract: This study assessed the effect of melatonin deprival on ovarian status and function in sheep. Experimental procedures were carried out within two consecutive breeding seasons. Animals were divided into two groups: pinealectomised (nZ6) and sham-operated (nZ6). The completeness of the pineal gland removal was confirmed by the plasma concentration of melatonin. Ovarian status was monitored by ovarian ultrasonography for 1 year to study reproductive seasonality. Follicular and corpus luteal growth dynamics were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 73 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…In Santa Inês sheep, raised in Brazil, melatonin nocturnal plasma concentration is higher in the autumn/winter than spring/summer (Coelho et al., ). Recent studies have provided strong evidence of the direct actions of melatonin on the ovaries in the corpus luteum, maintaining the production of progesterone (Taketani et al., ), and in the follicle, altering the pattern of follicular growth waves (Barros et al., ; Berlinguer et al., ; Maganhin et al., ; Manca et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Santa Inês sheep, raised in Brazil, melatonin nocturnal plasma concentration is higher in the autumn/winter than spring/summer (Coelho et al., ). Recent studies have provided strong evidence of the direct actions of melatonin on the ovaries in the corpus luteum, maintaining the production of progesterone (Taketani et al., ), and in the follicle, altering the pattern of follicular growth waves (Barros et al., ; Berlinguer et al., ; Maganhin et al., ; Manca et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…In Santa Inês sheep, raised in Brazil, melatonin nocturnal plasma concentration is higher in the autumn/winter than spring/summer (Coelho et al, 2006). Recent studies have provided strong evidence of the direct actions of melatonin on the ovaries in the corpus luteum, maintaining the production of progesterone (Taketani et al, 2011), and in the follicle, altering the pattern of follicular growth waves (Barros et al, 2013;Berlinguer et al, 2009;Maganhin et al, 2013;Manca et al, 2014). Gillan et al (1997) demonstrated that the best pregnancy indices are obtained by depositing the semen at the location and moment nearest to ovulation using a laparoscope since frozen semen has low viability in the female reproductive tract, surviving for approximately 6 hr after insemination (Gillan et al, 1997;Salamon & Maxwell, 1995;Watson, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The extension of discoloration was considered an index of total antioxidant activity of the sample. The TEAC level was calculated using Trolox as a standard (Re et al 1999, Manca et al 2014.…”
Section: Total Antioxidant Capacity Assaymentioning
confidence: 99%
“…In sheep maintained in temperate climates Thieíry et al (2003), found out that serum P 4 concentrations did not differ between varying day lengths following ovariectomy and CIDR treatment. However, in multiparous Sarda ewes (Italy), melatonin deficiency was associated with fewer emerging follicular waves during the induced estrous cycle, mainly because the average lifespan of all waves was longer in pinealectomized ewes compared with the control animals (Manca et al, 2014). Collectively, these observations may be interpreted to suggest that melatonin, in addition to its well-known effects on the secretion of GnRH, may directly influence the growth pattern of ovarian antral follicles.…”
mentioning
confidence: 92%